Valorization of recent arsenic removal methods and parameters controlled for testing: Mini review - N. A. A., Halem; Nurjannah, Salim; Siti Maznah, Kabeb; López-Mesas, M.; Nurlin, Abu Samah (Penerbit Universiti Malaysia Pahang, 2023)
This study presented the utilisation of an arsenic-ion imprinted polymer as an adsorbent to effectively eliminate arsenic compounds from water. Several variations of arsenic technique approaches have been described and the recent trends have been reviewed. The parameters investigated encompassed pH, temperature, duration of contact, dosage of adsorbent, initial concentration of arsenic ions, presence of competitive ions, and type of eluent in relation to the recovery process. The adsorption capability of the arsenic-ion imprinted polymer can be considerably influenced by pH and temperature.